1997
DOI: 10.1177/002204269702700205
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for Improving Methadone Treatment Process and Outcomes

Abstract: Major findings are summarized for a program of research focused on therapeutic enhancements to methadone treatment. Cognitive, behavioral, and psychoeducational strategies for improving client engagement and counseling services are described. Evaluations focused on during-treatment performance and follow-up outcomes collected 1 year after discharge, with an emphasis on the impact of services delivered as well as client and counselor perceptions of one another. Interrelations were examined between treatment pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(38 citation statements)
references
References 42 publications
1
36
1
Order By: Relevance
“…Older clients had better outcomes, whereas the more clients believed in the program, the longer they stayed, regardless of the clinic setting. Interestingly, "treatment process constructs" such as treatment satisfaction and counseling rapport, which have previously been found to be more important than belief in the program (Joe et al, 1999;Simpson & Joe, 1997), were not found to be significant predictors in this study. Treatment process constructs were already high for both those who remained in the program and those who dropped out.…”
Section: Rskocontrasting
confidence: 75%
“…Older clients had better outcomes, whereas the more clients believed in the program, the longer they stayed, regardless of the clinic setting. Interestingly, "treatment process constructs" such as treatment satisfaction and counseling rapport, which have previously been found to be more important than belief in the program (Joe et al, 1999;Simpson & Joe, 1997), were not found to be significant predictors in this study. Treatment process constructs were already high for both those who remained in the program and those who dropped out.…”
Section: Rskocontrasting
confidence: 75%
“…Dropping out of treatment correlated negatively with at least one positive individual change in the SCL-90 scales (r = -.338, p = .004), but not with the EuropASI Severity scales at intake. The predictor value of dropout seems to be small, but is in accordance with findings of other studies [32]. The relatively low dropout rate in the treatment as usual may be due to the more frequent treatment reactions to the individual risk of dropping out compared to the experimental treatment groups.…”
Section: Discussionsupporting
confidence: 90%
“…Dropout from treatment is a well-known negative predictor of treatment outcome in addiction [29,32]), but weeks in treatment could be more sensitive in separating the two groups. (2) Age, education, and gender are unclear predictors, but they are usually control variables to compare patient samples.…”
Section: Discussionmentioning
confidence: 99%
“…Establishing conceptual foundations representing the way treatment process and outcomes are related has been the primary focus of research summarized by the TCU Treatment Model (Simpson, 2001(Simpson, , 2004Simpson, Joe, Dansereau, & Chatham, 1997;. This model was created initially as a heuristic to integrate a body of research that accrued as part of several interrelated projects conducted over the past three decades (Simpson & Brown, 1999;Simpson, Joe, Rowan-Szal, & Greener, 1997;Simpson & Sells, 1982.…”
Section: Introductionmentioning
confidence: 99%